Enamel matrix derivative alone or in combination with a bioactive glass in wide intrabony defects - (:unkn) unknown (SPRINGER HEIDELBERG, 2006)
This controlled clinical study investigated the clinical and radiographic outcome of wide intrabony periodontal defects treated by enamel matrix derivatives alone or in combination with a bioactive glass over a period of 8 months. Twenty-three chronic periodontitis patients, who received initial therapy and had radiographical interproximal defects with an associated probing depth of 6 mm or more and an intrabony component of at least 4 mm, were included. Each of the patients, contributing at least one intrabony defect, was treated with either enamel matrix derivative alone (group 1, n=10) or the combination (group 2, n=13). In both groups, all clinical and radiographical parameters were improved. Groups 1 and 2 presented a mean pocket reduction of 5.03 +/- 0.89 and 5.73 +/- 0.80 mm, recession of 0.97 +/- 0.24 and 0.56 +/- 0.18 mm, relative attachment gain of 4.06 +/- 1.06 and 5.17 +/- 0.85 mm, and radiographic bone gain of 2.15 +/- 0.42 and 2.76 +/- 0.69 mm, respectively. An intergroup comparison revealed significant differences for all of the parameters, yielding a more favorable outcome towards the combined approach. Within the limits of the study, both treatments resulted in marked clinical and radiographical improvements, but combined treatment seemed to enhance the results in the treatment of wide intrabony defects.
Keywords: intrabony defects; periodontal regeneration; enamel matrix protein derivative; bone grafts; bioactive glass; GUIDED TISSUE REGENERATION; PERIODONTAL OSSEOUS DEFECTS; BOVINE-DERIVED XENOGRAFT; HISTOLOGIC EVALUATION; CLINICAL-EVALUATION; BONE DEFECTS; SPLIT-MOUTH; PROTEINS; HUMANS; EMDOGAIN(R)